The Influence of Selection and Financial Motivation on Employee Performance CV. Romen Sport through Competence as an Intervening Variable - Pradina, Lola Astrid; Firdaus, Vera; Andriani, Dewi (Universitas Pamulang, 2025)
This study aims to analyze the effect of Selection and Financial Motivation on employee performance of CV. Romen Sport through competence as an intervening variable. The type of research conducted by the author in this study is quantitative research, in quantitative research total sampling techniques are used in data collection. The location of the research conducted by the author to test the hypothesis is at the CV. Romen Sport Company which is located at Jl. Zainal Abidin, Gampang Village, Prambon District, Sidoarjo Regency, East Java. The number of respondents in this study were 83 people. This study uses the test Outer Model,Convergent Validity,Average Variance Extracted (AVE),Composite Reliability, Cronbach Alpha,Inner model,R Square,f-square,Q-square,Estimate for Path Coefficient.